PROBABILITY MODAL TRANSFER TO THE FORWARDER AT TERMINAL LAMONG BAY SURABAYA - Rezki Setya Irsadi; Hera Widyastuti (Institut Teknologi Sepuluh Nopember, 2017)
Currently the mobilization of freight transport from Surabaya to Jakarta or otherwise served by three types of modes transport, including truck, train, and marine vessels. But the majority of the freight transport cargo in the corridor Surabaya – Jakarta is served by trucking so that the impact on the capacity of roads and road load increases. The purpose of this study was to estimate the probability EMKL service manager / Forwarder to switch modes from container truck to railway mode container. The methods used to analyze the research data is a binary logistic regression. The results of these studies indicate that the travel time during the 3-day trip by truck containers will potentially probability modal transfer containers from trucks to rail containers reached 87.49%, and the more need for the use of container sizes of 20 ft. at a cost of Rp. 2,500,000 will potentially modal transfer containers from trucks to rail container by 82.34%, more than the container size of 40 ft. at a cost of Rp. 4,000,000 by 50%.